PENINGKATAN KOMPETENSI GURU MELALUI PEMANFAATAN KECERDASAN BUATAN (AI) DAN KONTEN INTERAKTIF H5P DALAM DESAIN PEMBELAJARAN - Nadia Lutfi Choirunnisa; Andi Kristanto; Utari Dewi; Hirnanda Dimas Pradana (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2026)
This community service program aims to enhance teachers’ competencies in designing instruction, conducting digital assessments, and developing technology-based innovative learning media. The program was implemented in Mojokerto through training on the use of artificial intelligence (AI) for formative and summative assessment, the use of interactive H5P content, the application of MagicSchool.ai in instructional design, and the development of interactive learning media at MTs Miftahul Ulum Kemlagi. The method employed was a descriptive design with a survey approach, conducted through workshops, mentoring, and hands-on practice. Based on survey results from 35 participants, 92% of teachers stated that the training materials were highly relevant to their professional needs, 88% demonstrated improved skills in developing interactive content, and 85% reported increased confidence in using technology-based learning media. This program had a positive impact on teachers’ readiness to face educational transformation in the digital era and contributed to strengthening digital literacy and innovation in 21st-century learning